Characterization of the branched chain amino acid metabolic pathway and its regulators in Aspergillus nidulans - Steyer, Joel T. (Kansas State University, 2022)
The branched chain amino acids (BCAAs) isoleucine, leucine, and valine are essential amino acids because they are not synthesized by mammals. Many fungal species, including Aspergillus, Magnaporthe, Fusarium, and Candida are capable of de novo BCAAs synthesis. Crop and human pathogens, such as Magnaporthe oryzae and Aspergillus fumigatus, respectively, require BCAAs for full pathogenicity. BCAA pathway enzymes and transcriptional regulators are potential targets for anti-fungal treatments as treatments can target the pathogen without harming its host. In this dissertation, the model eukaryotic filamentous fungus Aspergillus nidulans is used to complete the BCAA biosynthetic pathway and characterize transcription factors that regulate the BCAA pathway. The first part of this dissertation focuses on analysis of the full BCAA biosynthesis pathway in A. nidulans. The final step in BCAA biosynthesis and first step in BCAA catabolism is catalyzed by branched chain amino acid aminotransferase (BAT) enzymes. A. nidulans encodes six putative bat genes. Separate deletion of each bat gene indicated that each is dispensable. Two of the bat genes play a role in secondary metabolite production so the roles of the remaining four bat genes were the focus of this work. Double, triple, and quadruple deletion mutants of the four bat genes were constructed. Deletion of both batA and batB in the double, triple, or quadruple deletion mutants confers tight BCAA auxotrophy, revealing that both genes act in BCAA biosynthesis. The batA and batB genes were also the two most highly expressed bat genes. Furthermore, the biosynthetic and catabolic profiles for each enzyme were characterized, batA primarily being biosynthetic and batB primarily catabolic. During this research, spontaneous suppressor mutants of the batA batB double deletion mutant arose and these new mutants were BCAA prototrophs. To determine the genetic mutation that suppressed the BCAA auxotrophy, Whole Genome Sequencing was performed on ten independent spontaneous suppressor mutants. Single Nucleotide Polymorphism (SNP) analysis revealed that all ten spontaneous suppressor mutants had mutations in six genes. One of these genes, which is currently uncharacterized in A. nidulans, contains a SPT2 domain sequence. SPT2 domains are associated with transcriptional regulation in hypoxic conditions. Disruption of the SPT2 domain may de-repress expression of genes that are normally repressed during oxygen-replete conditions, and de-repression of an unknown gene may overcome the BCAA auxotrophy of the batA batB double mutant. The second part of this research focused on understanding the transcriptional regulation of the BCAA pathway genes. In A. nidulans, the transcription factor LeuB regulates leucine biosynthesis genes and the major nitrogen assimilation gene, gdhA. The leuB deletion mutant is a partial leucine auxotroph, meaning it grows poorly without exogenous leucine. One explanation is that another transcription factor may also activate leucine biosynthesis genes. A. nidulans encodes two additional transcription factors with sequence similarity to LeuB. To further understand the relationship between LeuB and its paralogs, phylogenetic analysis was performed. LeuB is more broadly conserved than the other two transcription factors. The more closely related transcription factor was named LeuR and it was hypothesized that LeuR regulation accounted for the partial leucine auxotrophy observed in the leuB deletion mutants. The leuR deletion mutant is a leucine prototroph. However, the leuB leuR double deletion mutant shows tight leucine auxotrophy indicating a role for LeuR in regulation of leucine biosynthesis. To characterize the function of LeuR, reporter gene assays were utilized to determine if LeuR also regulates transcription of the important nitrogen assimilation gene gdhA, which encodes NADP-glutamate dehydrogenase. gdhA-lacZ reporter gene assays showed that LeuR, in the absence of LeuB, regulates gdhA. Using promoter-deletion strains, the regions where LeuR acts were narrowed to two sites. These sites of action are also shared by LeuB, indicating conservation of sites of action between the two transcription factors. Additionally, RNA-Seq was used to characterize the genome-wide regulation of A. nidulans by LeuB and LeuR to determine which gene targets they regulate. The research detailed in this dissertation builds the framework of the branched chain amino acid biosynthetic pathway and the major regulators of the pathway, showcasing which enzymes and transcription factors are the most prudent potential antifungal targets. This research highlights the need for in-depth analysis to reveal the roles of paralogous genes as we show that loss of one functional gene does not cause BCAA auxotrophy. Therefore, incomplete disruption of the pathway or its regulation by anti-fungal treatments may cause adaptation and resistance rendering such anti-fungal agents ineffective.
Keywords: Fungal metabolism; Genetics; Transcription